PENGARUH KOMUNIKASI PEMASARAN TERPADU TERHADAP CITRA PERUSAHAAN DAN DAMPAKNYA TERHADAP KEPUASAN PELANGGAN MEMBELI MOBIL PADA P.T. HADJI KALLA CABANG PALU - Akkas, Nasruhlhak (Katalogis, 2016)
This study is aims: 1) to seek and analyze the influence of Integrated Marketing Communication on corporate image of P.T. Hadji Kalla, Branch of Palu and 2) to seek and analyze the influence of corporate image on customer satisfaction in buying cars in P.T. Hadji Kalla, Branch of Palu. The research method is causal-descriptive. Population of the study consists of people who bought cars from P.T. Hadji Kalla, Branch of Palu and 180 people selected as samples throught probability sampling with systematic sampling. Method of analysis is quantitative descriptive and the analisis tool is Structure Equation Modeling (SEM). the results show that; 1) Integrated Marketing Communication positive and significant influence on P.T. Hadji Kalla’s image; 2) corporate image positive and significant influence on customer’s satisfaction in buying cars in P.T. Hadji Kalla, branch of Palu.